Communication strategies and public perceptions : a study of the National Trade Union Congress of Singapore. - Tan, Steve Peng Hoe. (2008)
An examination of the structure, functions, employee perception and public perception of the NTUC, in particular its raison d'etre and whom it represents. The objective is to gain an in depth understanding with empirical data to support the issue of their perceptions and recommend suitable strategies for the development of the organization.